SOCIAL MEDIA CONTENT AS A MEDIUM TO PROMOTE AGRICULTURE TO GEN Z BY @TANDURIA - Nasir, Fuad; Gissani, Muhammad Fikri; Al Mujib, Ihwan Huda (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2025)
This study explores the role of social media content—particularly YouTube Shorts—on the Tanduria channel in promoting agriculture among Generation Z. Given Indonesia's status as an agricultural nation, concerns about the lack of farmer regeneration, especially among youth, have become increasingly urgent. This study aims to understand how digital communication strategies can enhance interest in agriculture within this demographic. Utilizing a qualitative descriptive method, data were collected through interviews, content analysis, and literature review. The findings reveal that Tanduria successfully engages Gen Z by using informal and relatable language, branding itself with the urban farming concept, and presenting practical, informative, and entertaining short videos. The channel also integrates commercial elements such as product promotions without disrupting educational value. Communication strategies such as personal greetings, humorous tones, and culturally resonant jargon contribute to high engagement. Moreover, the use of real-life demonstrations and DIY tips adds authenticity and practicality, aligning with Gen Z’s preferences for accessible and action-oriented content. This research concludes that social media, especially short video platforms, can serve as an effective medium to bridge the gap between agriculture and younger generations. The study contributes to the discourse on digital communication for agricultural promotion, offering insights for stakeholders aiming to attract youth involvement in this sector.